Homobivalent Dopamine D2Receptor Ligands Modulate the Dynamic Equilibrium of D2Monomers and Homo-and Heterodimers - Ullmann, Tamara; Gienger, Marie; Budzinski, Julian; Hellmann, Jan; Hübner, Harald; Gmeiner, Peter; Weikert, Dorothée (ACS Chemical Biology, 2021)
Dopamine D2 receptors (D2Rs) are major targets in the treatment of psychiatric and neurodegenerative diseases. As with many other G protein-coupled receptors (GPCRs), D2Rs interact within the cellular membrane, leading to a transient receptor homo-or heterodimerization. These interactions are known to alter ligand binding, signaling, and receptor trafficking. Bivalent ligands are ideally suited to target GPCR dimers and are composed of two pharmacophores connected by a spacer element. If properly designed, bivalent ligands are able to engange the two orthosteric binding sites of a GPCR dimer simultaneously. Taking advantage of previously developed ligands for heterodimers of D2R and the neurotensin receptor 1 (NTSR1), we synthesized homobivalent ligands targeting D2R. Employing bioluminescence resonance energy transfer, we found that the bivalent ligands 3b and 4b comprising a 92-atom spacer are able to foster D2R-homodimerization while simultaneously reducing interactions of D2R with NTSR1. Both receptors are coexpressed in the central nervous system and involved in important physiological processes. The newly developed bivalent ligands are excellent tools to further understand the pharmacological consequences of D2R homo-and heterodimerization. Not limited to the dopaminergic system, modifying class A GPCRs' dynamic equilibrium between monomers, homomers, and heteromers with bivalent ligands may represent a novel pharmacological concept paving the way toward innovative drugs.
CRIS-Team Scopus Importer:2021-02-05